2013
DOI: 10.1111/dote.12032
|View full text |Cite
|
Sign up to set email alerts
|

Differential clinical and pathological characteristics of esophageal stromal tumors and leiomyomata

Abstract: The objective of the study was to assess the differences in clinical and pathological characteristics between esophageal stromal tumor and leiomyoma. Data from 93 esophageal stromal tumors and leiomyomata cases were retrospectively analyzed, including clinical symptoms, endoscopic features, pathological characteristics, immunohistochemistry (IHC), and treatment. All cases underwent endoscopic ultrasonography examination before treatment. Lesions arising from the muscularis mucosa were resected by endoscopic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the presence of TCs was recently documented within stroma of different segments of the gastrointestinal tract . Noteworthy, the oesophageal stroma is an active participant to several disorders . Moreover, it was previously suggested that TCs, by their ultrastructural features and paracrine secretory potential, might represent the origin of PEComa and GISTs in digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of TCs was recently documented within stroma of different segments of the gastrointestinal tract . Noteworthy, the oesophageal stroma is an active participant to several disorders . Moreover, it was previously suggested that TCs, by their ultrastructural features and paracrine secretory potential, might represent the origin of PEComa and GISTs in digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, esophageal submucosal tumors with smooth mucosa might always not be benign . Endoscopic and EUS finding cannot accurately distinguish between esophageal leiomyomas and GISTs . For these reasons, some patients who present with small SELs prefer resection.…”
Section: Discussionmentioning
confidence: 99%
“…31 Endoscopic and EUS finding cannot accurately distinguish between esophageal leiomyomas and GISTs. 32 For these reasons, some patients who present with small SELs prefer resection. Leiomyoma 6 None 2 Male 33 6 Middle Leiomyoma 13 None 3 Female 47 6 Lower Leiomyoma 15 None 4 Male 42 7 Lower Leiomyoma 9 None 5 Male 42 5 Middle Leiomyoma 17 None 6 Male 66 12 Lower GIST 16 Bleeding 7 Male 63 11 Middle Leiomyoma 15 None 8 Female 57 10 Middle Leiomyoma 8 None 9 Male 59 Recently, technical advances in EUS as well as new devices designed for endoscopic resection have opened up the field to many therapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…They usually appear as a solitary smooth flat or hemispheric bulge with intact overlying mucosa ( Fig. 28.7) [76]. Some may be annular and encircle the esophagus.…”
Section: Endoscopic and Endosonographic Featuresmentioning
confidence: 99%